2017
DOI: 10.1159/000455236
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Hidradenitis Suppurativa in a Cohort of Patients in Southern Finland: A Pilot Study

Abstract: Background: Hidradenitis suppurativa (HS) is a chronic inflammatory disease that impacts the quality of life. Methods: We evaluated its burden in a cohort of 26 Finnish patients in a single-center cross-sectional study. Demographic data, disease history, clinical data, treatment patterns, and workability were collected. Patients responded to the Dermatology Life Quality Index (DLQI) and Beck Depression Inventory (BDI-21). Results: Mean age of HS patients was 44.2 years and mean diagnostic delay was 13.7 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 16 publications
4
32
0
Order By: Relevance
“…80 A high Hurley stage and female gender were variables that significantly correlated with the total DLQI score in a Finnish study of HS patients. 81 Women in that study had consistently higher scores than men for every item of the DLQI. There was no significant correlation between resilience and HRQoL in HS patients from the United States and Denmark.…”
Section: Validation Of Hs-specific Qol Instrumentsmentioning
confidence: 64%
“…80 A high Hurley stage and female gender were variables that significantly correlated with the total DLQI score in a Finnish study of HS patients. 81 Women in that study had consistently higher scores than men for every item of the DLQI. There was no significant correlation between resilience and HRQoL in HS patients from the United States and Denmark.…”
Section: Validation Of Hs-specific Qol Instrumentsmentioning
confidence: 64%
“…These studies have reported a prevalence ranging from 0.078 to 4% [4][5][6] at a female:male ratio of approximately 3: 1 [4][5][6][7]. The cause for the female predominance is uncertain, but postulated reasons include differences in self-care (such as shaving of hair-bearing sites), in hormones or in health-seeking behaviour [8].…”
Section: Introductionmentioning
confidence: 99%
“…Ten patients (38.5%), of whom 9 were women, reported depression symptoms (BDI-21 >12); mild, moderate, and severe depression was reported in 6, 2, and 2 patients, respectively. The DLQI and BDI-21 results are discussed in detail elsewhere [8]. …”
Section: Resultsmentioning
confidence: 99%
“…The study enrolled adult patients diagnosed with HS. The inclusion criteria, study methodology, and main study results are reported in more detail elsewhere [8]. The patients' HRQoL was compared to that of a representative sample of an age-standardized general population ( n = 4,176) from the Health 2011 Health Examination Survey [6] and to that of age-standardized psoriasis patients ( n = 138) from the Health 2000 Health Examination Survey [7].…”
Section: Methodsmentioning
confidence: 99%